PENGARUH HUMAN CAPITAL DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS LINGKUNGAN HIDUP KOTA TERNATE - rajak adn nan; Muhammad Thahrim; Maeda Pinoa (Jurnal Manajemen Sinergi, 2018)
The purpose of this study to determine the effect of Human Capital and Job Satisfaction either partially or simultaneously on the performance of employees of the Office of the Environment in Ternate. The analysis model used to test the hypothesis is multiple linear regression analysis, and the research method used is explanatory research with quantitative approach and sample of 69 respondents. With data processing techniques using SPSS 16 for windows. The results of the study prove that: (1) Human Capital has a positive and significant influence on Employee Performance, which means that the better human capital, the better the performance of employees. (2) Job Satisfaction has a positive and significant influence on Employee Performance, which means that the higher level of employee job satisfaction will give satisfaction to the performance. With the simultaneous results of both variables have a positive and significant effect on Employee Performance with R2 (R Square) corrected by 0.574 or 57.4%.